Combination of a biodegradable three-dimensional (3D) – printed cage for mechanical support and nanofibrous membranes for sustainable release of antimicrobial agents for treating the femoral metaphyseal comminuted fracture. (August 2017) - Chou, Ying-Chao; Lee, Demei; Chang, Tzu-Min; Hsu, Yung-Heng; Yu, Yi-Hsun; Chan, Err-Cheng; Liu, Shih-Jung
Abstract: The aim of this study was to develop a biodegradable three-dimensional-printed polylactide (PLA) cage for promoting bony fixation and an antibiotics-embedded poly(d, l )-lactide-co-glycolide (PLGA) nanofibrous membrane for infectious prophylaxis during treating the comminuted metaphyseal fracture in a rabbit femoral model. The in vitro studies included measuring the mechanical properties of the 3D printed cage and determining release activities of vancomycin and ceftazidime from the nanofibers. The in vivo study included comparisons of rabbits of the femoral metaphyseal comminuted fracture treated with or without the combined biodegradable polymers. The results showed that vancomycin and ceftazidime were sustainably detected above the effective levels in the local tissue fluid around the fracture site for 3 weeks. The animal studies showed that rabbits with the 3D cage implantation possessed better cortical integrity, leg length ratio, and maximal bending strengths. The study results indicate that these combined polymers may promote fracture fixation during treating the rabbit femoral metaphyseal comminuted fracture. Graphical abstract: Highlights: Comminuted metaphyseal fractures put significant burden on orthopedic surgeons. A biodegradable three-dimensional-printed polylactide (PLA) cage promotes bony fixation Antibiotics-embedded poly(d, l )-lactide-co-glycolide (PLGA) nanofibers prevent infection during treating fractures.